Social representations of the territory in the Committee for the Defense of Water and the Páramo de Santurbán Colombia (2010-2017) - Guauque, César (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article constitutes a partial advance within the research project “Social representations of the territory in the conflict over the delimitation of the páramo de Santurbán (Colombia), years 2010-2017”, and as such inquires about the importance of the mining-environmental conflict in the formation of social representations of the territory that in the discursive plane contribute within the process of articulation of the committee, one of the main actors in this dispute. The objective is the configuration of the significance framework about the territory present in the committee's speech at the different moments of the conflict. For this purpose, it proposes a methodological approach of a qualitative type that takes as an approach the analysis of discourse.  The understanding of the space / territorial object is characterized through the subjective, intersubjective and transubjective dimensions of discourse, each of which has its own elements and indicators. The result is a form of symbolic cartography that brings together the nuclear and peripheral elements of the social representations of the territory deployed from this actor, which have a great importance, as a symbolic resource, in the dispute over the delimitation of the páramo.